INCIDENTAL SQUAMOUS CELL CARCINOMA OF THE RENAL PELVIS IN A NONFUNCTIONING KIDNEY THAT WAS MISSED ON TWO NON-CONTRAST CT-SCANS - Hassan, Masroor; Qureshi, Asim (Journal of Ayub Medical College Abbottabad, 2017)
Although the second most common malignancy after urothelial carcinoma, squamous cell carcinoma (SCC) of the renal pelvis is a rare entity. It has strong association with nephrolithiasis thus emphasizing prompt treatment of renal calculi. Because of rarity and nonspecific clinical and radiological findings, it mostly presents at pT3 or higher stage. We report SCC of renal pelvis that was missed two times on non-contrast CT scans and was diagnosed incidentally in a nephrectomy specimen. Its prognosis is similar to that of urothelial carcinoma of comparable stage. Owing to its rarity, no standard treatment guidelines are available, however radical nephrectomy with lymph node dissection is the initial treatment which can be curative in an early stage disease. Adjuvant chemotherapy and radiotherapy are usually ineffective. Keywords: Squamous cell carcinoma, Imaging, Schistosoma haematobium